Optical sensor-based nitrogen management: an environmentally friendly and cost-effective approach for sustainable wheat (Triticum aestivum L.) production on Eastern plains of India - Mitra, Biplab; Singha, Prantick; Roy Chowdhury, Arnab; Sinha, Abhas Kumar; Skalicky, Milan; Laing, Alison M.; Alamri, Saud; Hossain, Akbar (Frontiers in Sustainable Food Systems, 2023)
Optical sensor like Green Seeker (GS) is an emerging tool for site-specific in-season fertilizer nitrogen management strategy. The objective of this study was to establish an in-season estimate of yield (INSEY)-grain yield (GY) relation in wheat grown under eastern plains of India using normalized difference vegetation index (NDVI) at 45 and 65 days after sowing (DAS). Data revealed lower NDVI values at 65 DAS over 45 DAS in no-NPK applied control plots as well as in N-rich plots (225 kg ha-1 N); on the contrary, the values were higher at 65 DAS over 45 DAS in treatments where some N fertilizers were added based on NDVI readings at 45 DAS. Response index (RI) showed higher chances of response to external application of N in NDVI-based treatments. The INSEY- GY relation for wheat at 45 and 65 DAS were worked out as a power function of y = 64265x1.171 and y = 46949x1.036 (y is the attainable yield in kg ha-1 and x is INSEY), respectively. The yields could fairly be predicted through this relation even at 45 DAS; though the relation was more robust at 65 DAS (R2=0.94). A prescriptive dose of 60 kg N ha-1 as basal + 60 kg N ha-1 at crown root initiation (CRI) stage followed by NDVI sensor guided N application (at 45 and 65 DAS) brought about a significant improvement in yield performances, N use efficiencies with higher net returns and benefit-cost ratio. The results proved the reliability of the NDVI sensor as an important tool for the optimization of fertilizer nitrogen in wheat grown under the eastern plains of India. The new INSEY-GY relation developed through this trial could successfully be used for yield prediction in the eastern plains of India under changing climate.